Digitization of conferences between development requirements and the specter of failure (Analytical study in light of the COVID-19 crisis) - Al-Alami, Iman (Journal of Economic, Administrative and Legal Sciences, 2021)
In light of the Covid 19 crisis, the telecommunications sector is no longer limited to traditional communication and searching for information, but rather the trend to communicate via the Internet, and this trend has gained great strength and spread and as a result, we see today digital conferences where individuals participate for predetermined hours, to cover a broad topic, such as blogging or education. Or medicine or technology. The process of digital transformation in conferences is very sensitive in light of the Covid 19 crisis, while most of the economic literature in this field has focused on the success factors of digital conferences as an alternative to direct meetings under conditions of divergence and quarantine, the factors of failure and failure are left aside, This is what prompted us to prepare this paper, through which we aim to shed light on the digital transformation of conferences and the specter of failure threatening them in light of the Covid 19 crisis, referring to the state of conferences for some countries and companies in a study of the impact of this on achieving success for their digital conferences.